The six-month line in geomagnetic long series - J. L. Le Mouël (Annales Geophysicae, 2004)
Daily means of the horizontal components X (north) and Y (east) of the geomagnetic field are available in the form of long series (several tens of years). Nine observatories are used in the present study, whose series are among the longest. The amplitudes of the 6-month and 1-year periodic variations are estimated using a simple but original technique. A remarkably clear result emerges from the complexity of the geomagnetic data: the amplitude of the 6-month line presents, in all observatories, the same large variation (by a factor of 1.7) over the 1920–1990 time span, regular and quasi-sinusoidal. Nothing comparable comes out for the annual line. The 6-month line results from the modulation by an astronomical mechanism of a magnetospheric system of currents. As this latter mechanism is time invariant, the intensity of the system of currents itself must present the large variation observed on the 6-months variation amplitude. This variation presents some similarities with the one displayed by recent curves of reconstructed solar irradiance or the "Earth's temperature". Finally, the same analysis is applied to the aa magnetic index. Key words. Geomagnetism and paleomagnetism (time variations, diurnal to secular). Magnetospheric physics (current systems; polar cap phenomena)